Opioid Use in the Management of Diabetic Peripheral Neuropathy (DPN) in a Large Commercially Insured Population. Issue 5 (May 2015) - Patil, Pravinkumar R.; Wolfe, Jonathan; Said, Qayyim; Thomas, Jeremy; Martin, Bradley C.
<x xml:space="preserve">Abstract</x> Objective: To examine the proportion of diabetic peripheral neuropathy (DPN) patients receiving pharmacologic DPN treatments and specifically to identify the rates and factors associated with opioid use and first-line opioid use. Methods: A 10% sample of IMS-LifeLink claims data from 1998 through 2008 was used. The study population consisted of diabetic patients who met DPN criteria using a validated DPN algorithm. Multivariable logistic regression controlling for demographics, comorbidities, and other clinical characteristics was used to identify factors associated with any DPN pharmacologic treatment, any opioid use, and first-line opioid treatment. Sensitivity analyses were conducted to explore variations in exclusion criteria as well as opioid use definitions. Results: A total of 666 DPN patients met inclusion criteria and pharmacologic treatment was received by 288 patients (43.24%) and of those, 154 (53.47%) had DPN-related opioid use and 96 (33.33%) received opioid as first-line treatment. Persons with diabetic complications were more likely to use opioids (odds ratio=4.53; 95% confidence interval, 1.09-18.92). Food and Drug Administration-approved DPN agents duloxetine 1.04% (n=3) and pregabalin 5.56% (n=16) had much lower rates of use. DPN-related drug use and DPN-related opioid usage increased as we used less restrictive samples in sensitivity analyses. Conclusions: Opioids were the most frequently prescribed first-line agents for DPN. More than 50% of DPN patients remained untreated with pharmacologic agents 1 year after a DPN diagnosis.